2020
DOI: 10.18632/aging.102660
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of epithelial-mesenchymal transition markers in clear cell renal cell carcinoma

Abstract: Epithelial-to-mesenchymal transition (EMT) is important in tumor invasiveness and metastasis. We aimed to determine prognostic value of six key EMT markers (CDH1, CDH2, SNAI1, SNAI2, VIM, TWIST1) in clear cell renal cell carcinoma (ccRCC). A total of 533 ccRCC patients with RNASeq data from The Cancer Genome Atlas (TCGA) cohort were included for analysis. Gene expression of these EMT markers was compared between tumor and normal tissues based on Oncomine database and TCGA cohort. Their correlations with progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 45 publications
2
14
0
Order By: Relevance
“…Importantly, our study provides supporting evidence that certain hypoxia-related genes are associated with a lower survival in RCC patients-that is, IRS2, ROR2, and ENO2 [35,38,39]. Moreover, the RNA-Seq analysis coupled with the interrogation of the TCGA KIRC dataset allowed the identification of novel candidates strongly associated with poor prognosis and the lethal evolution of RCC, including NUMBL, COL6A1, and ASPM, as well as SNAI2 [51]. The specific impact of each gene in the setting of RCC, hypoxic, and pseudo-hypoxic contexts should be investigated in future studies.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Importantly, our study provides supporting evidence that certain hypoxia-related genes are associated with a lower survival in RCC patients-that is, IRS2, ROR2, and ENO2 [35,38,39]. Moreover, the RNA-Seq analysis coupled with the interrogation of the TCGA KIRC dataset allowed the identification of novel candidates strongly associated with poor prognosis and the lethal evolution of RCC, including NUMBL, COL6A1, and ASPM, as well as SNAI2 [51]. The specific impact of each gene in the setting of RCC, hypoxic, and pseudo-hypoxic contexts should be investigated in future studies.…”
Section: Discussionsupporting
confidence: 65%
“…TGFB1 is known to have a central role in the regulation of EMT, fibrosis, stem cell maintenance, invasiveness and metastatic development [46][47][48]. SNAI2, also known as Slug, is a well-known EMT transcription factor that is critically involved in oncogenesis and in the maintenance of stemness and progenitor cells [49][50][51]. COL6A1 is a member of the collagen family that is involved in numerous biological processes, including apoptosis, autophagy, stemness, differentiation, and tumor progression, including in RCC [52,53].…”
Section: R167q Vhl Mutation Regulates Genes Associated With Poor Prognostic and Overall Survivalmentioning
confidence: 99%
“…Krebs et al reported that ZEB1, an EMT transcription factor, is closely associated with tumor grade, invasion, metastasis and tumor progression in mouse pancreatic cancer model [30]. Studies have shown that higher expressions of Vimentin and TWIST1 and lower expression of E-cadherin are associated with high tumor grade, poor prognosis and worse progression-free survival in renal cancer patients [31,32]. In addition to triggering metastatic properties, EMT is also known to be associated with drug resistance in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we found that the Slug gene, which is a potent regulator of the EMT pathway, has a speci c HOXA5-binding sequence in its promoter region. EMT, which plays a crucial role during embryogenesis [31], was rst described in the 1980s. Cells that undergo EMT lose their epithelial morphology and acquire stronger mobility, facilitating migration, and EMT may also regulate the invasion of cancer cells [32].…”
Section: Discussionmentioning
confidence: 99%